Rapunzel syndrome in surgical emergency managing dual trichobezoars in a patient with cerebral palsy - Saini, Abhishek; Balamurugan, S (Indian Journal of Case Reports, 2025)
Rapunzel syndrome, a rare form of trichobezoar, may lead to significant bowel obstruction. The patient often presents with features of bowel obstruction, such as vomiting, abdominal pain, and distention. We report the case of a 13-year-old female with cerebral palsy who arrived at the emergency department with symptoms indicative of gastric outlet obstruction. Diagnostic imaging and laparotomy revealed two large trichobezoars, causing concurrent obstruction at the gastric outlet and in the small bowel. Given the association with psychiatric conditions such as trichophagia, post-surgical psychiatric evaluation was arranged to address the underlying behavior and minimize recurrence risk. This case highlights the critical role of an integrated diagnostic and therapeutic approach for effective management in these patients.